Strengthening Capacity Of “Sarining Trigona Pertiwi” Beekeeper Through International Networking - Mangku, I Gede Pasek; I Gusti Bagus Udayana; I Made Suwitra; Luh Kade Datrini; Amelia R. Nicolas; Hanilyn A. Hidalgo; Mia Bella R. Fresnido (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The development of small-scale honey beekeeping businesses relies on strong networking, effective marketing, and knowledge transfer. This community service program aimed to strengthen the capacity of the Sarining Trigona Pertiwi beekeeping group in Bongkasa Pertiwi Village, Bali, through international collaboration. In partnership with Central Bicol State University of Agriculture (CBSUA) and the Beekeeper Association of Camarines Norte (BACN) from the Philippines, the program facilitated knowledge exchange on Trigona bee cultivation, honey production, post-harvest handling, and market expansion strategies. The program employed mentoring, skill development, and networking activities involving 49 participants, including beekeepers, university experts, and local government officials. The results showed that international mentoring and collaboration significantly enhanced the group's knowledge, promotional strategies, and market access. Strengthening networking at regional and global levels also created new opportunities for sustainable honey production and tourism-based economic development (Melitourism). The findings highlight the importance of ongoing capacity-building programs to ensure the resilience and competitiveness of small-scale honey businesses in Indonesia. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals